The Strategy of Implementation Integration Intelligent Tutoring System in Iraq Education System - Alkhuwaylidee, Ahmed Rashid (Technium Sustainability, 2025)
The topic of integrating Intelligent Tutoring Systems, specifically for education in Iraq within this article is an urgent area of interest due to the necessity to modernize and enhance education infrastructure. The paper discusses the opportunities and challenges, as well as the level of readiness for ITS in Iraq given its educational environment and technology infrastructure. This study examines how ITS can be a solution to the unique problems of Iraqi education like the low quality of schools in rural areas with poor accessibility, minimizing shortage of teachers and providing personalized learning methods to fill up knowledge gaps caused by years of war. This article starts with an overview of ITS technology and its applications in education, then sheds some light on the current situation of the Iraqi education system detailing its strengths and weaknesses as well as reform efforts. The subsequent part takes a deeper dive into the promises ITS suggests in the Iraqi setting, illuminating how these systems could enable learner-driven instruction and improve teacher effectiveness while offering guidance to evidence-based educational policymaking. The study also provides examples of some ITS trials, particularly at a university level within Iraq and with International partners. I hope by learning from those examples, we can validate the possibility and the impact of the use of ITS in the Iraqi educational scene. The article also reviews the barriers to the uptake of ITS in Iraq such as infrastructure limitations, digital illiteracy and cultural and linguistically sensitive content.